2018
DOI: 10.1371/journal.pmed.1002655
|View full text |Cite
|
Sign up to set email alerts
|

Safety and pharmacokinetics of single, dual, and triple antiretroviral drug formulations delivered by pod-intravaginal rings designed for HIV-1 prevention: A Phase I trial

Abstract: BackgroundIntravaginal rings (IVRs) for HIV pre-exposure prophylaxis (PrEP) theoretically overcome some adherence concerns associated with frequent dosing that can occur with oral or vaginal film/gel regimens. An innovative pod-IVR, composed of an elastomer scaffold that can hold up to 10 polymer-coated drug cores (or “pods”), is distinct from other IVR designs as drug release from each pod can be controlled independently. A pod-IVR has been developed for the delivery of tenofovir (TFV) disoproxil fumarate (TD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Using this binary combination, we achieved full protection from simian/human immunodeficiency virus (SHIV) infection in the rigorous, repeat low-dose vaginal exposure model using normally cycling female pigtailed macaques 29 as well as from vaginal and rectal HIV-1 infection in humanized BLT mice 27 . We also showed that topical delivery of the combination from an intravaginal ring (IVR) was safe in a Phase I clinical trial ( N = 6) and led to drug concentrations in vaginal fluids and tissues exceeding those obtained by highly protective oral dosing, suggesting that efficacy for vaginal HIV-1 PrEP is achievable 30 . The TDF-FTC IVRs also led to unexpectedly high drug concentrations in rectal fluids, indicating that dual-compartment protection HIV-1 infection during both vaginal and receptive anal intercourse may be possible with minimal systemic drug exposure 31 .…”
Section: Discussionmentioning
confidence: 98%
“…Using this binary combination, we achieved full protection from simian/human immunodeficiency virus (SHIV) infection in the rigorous, repeat low-dose vaginal exposure model using normally cycling female pigtailed macaques 29 as well as from vaginal and rectal HIV-1 infection in humanized BLT mice 27 . We also showed that topical delivery of the combination from an intravaginal ring (IVR) was safe in a Phase I clinical trial ( N = 6) and led to drug concentrations in vaginal fluids and tissues exceeding those obtained by highly protective oral dosing, suggesting that efficacy for vaginal HIV-1 PrEP is achievable 30 . The TDF-FTC IVRs also led to unexpectedly high drug concentrations in rectal fluids, indicating that dual-compartment protection HIV-1 infection during both vaginal and receptive anal intercourse may be possible with minimal systemic drug exposure 31 .…”
Section: Discussionmentioning
confidence: 98%
“…More recently, a dapivirine ring for HIV prevention demonstrated moderate efficacy for HIV pre-exposure prophylaxis (PrEP) [8, 9] and is under review by the European Medicines Agency, with upcoming regulatory submissions to the US Food and Drug Administration and South African Health Products Regulatory Authority. Other VRs for HIV PrEP and multi-purpose prevention technologies (MPTs) are at various stages in the development pipeline [8, 1013]. MPT VRs are particularly promising, as they increase efficiencies for users and health systems by simultaneously addressing multiple sexual and reproductive health needs [14].…”
Section: Introductionmentioning
confidence: 99%
“…52 It will be important to promote clear public health advice on this topic going forwards, particularly with the potential advent of new evidence-based intravaginal devices such as antiretroviral intravaginal rings for HIV pre-exposure prophylaxis which have been undergoing clinical trials. [59][60][61]…”
Section: Journal Of Global Health Reportsmentioning
confidence: 99%